Guía para la implementación de un sistema de gestión de calidad basado en ISO 9001:2015 en Universal Química Andina S.A.S (2022)
The objective of this degree work was to design a guide that allows the Universal Química Andina SAS company to implement a Quality Management System based on the ISO 9001: 2015 standard, the guide is built from a diagnosis developed using a checklist that makes it possible to consolidate what items the company has, what it would need to reach 100% of the item and what areas would be part of its construction. For the development of any activity, it is necessary for the company's directors to fully develop number 4 and recognize the internal and external context of the company, proposing ambitious, achievable strategic objectives that align all the areas belonging to the organization.